Immunomodulator loaded microneedle arrays for targeted intradermal drug delivery to skin tumors - Akmal H. Sabri; Fiona Smith; Zachary Cater; Pratik Gurnani; Ami Nash; Victoria Brentville; Lindy Durrant; John McKenna; Joel Segal; David J. Scurr; Maria Marlow (Drug Delivery)
Topical therapy with imiquimod in a cream [5% w/w imiquimod cream (Aldara™)] for the treatment of nodular basal cell carcinoma (BCC) currently results in low cure rates, attributed to low imiquimod permeation. Herein we have developed novel microneedle array patches (MAPs), to maximize imiquimod intradermal delivery and retention in the skin, with potential as an efficacious treatment for BCC. Enhanced delivery of imiquimod in pig skin and ex vivo BCC tissue was found with the obelisk poly N-acryloylmorpholine (pNAM) MAPs as compared to the 5% w/w imiquimod cream and MAPS manufactured from a commercially available polymer (PVPVA). Additionally, the increased retention in ex vivo BCC tissue was found with the obelisk pNAM MAPs as compared to the 5% w/w imiquimod cream. In addition, detailed characterization of single needles and mechanistic studies of MAPs in tissue using mass spectrometry imaging confirmed the imiquimod homogeneity in the needles. Most importantly, the in vivo tumor efficacy study showed that pNAM obelisk MAPs could deliver imiquimod into the tumor, retarding tumor growth. This study suggests that the drug loaded obelisk pNAM MAPs manufactured here may be of clinical utility for localized intradermal delivery of imiquimod.